Anthropogenic underwater vibrations are sensed and stressful for the shore crab Carcinus maenas. (15th September 2021) - Aimon, Cassandre; Simpson, Stephen D.; Hazelwood, Richard A.; Bruintjes, Rick; Urbina, Mauricio A.
Abstract: Acoustic pollution in aquatic environments has increased with adverse effects on many aquatic organisms. However, little work has been done considering the effects of the vibratory component of acoustic stimuli, which can be transmitted in the substrate and propagated into the aquatic medium. Benthic marine organisms, including many invertebrates, are capable of sensing seabed vibration, yet the responses they trigger on organism have received little attention. This study investigates the impact of underwater vibration on the physiology and behaviour of a ubiquitous inhabitant of coastal areas of the northern hemisphere, the shore crab Carcinus maenas . We developed a novel vibratory apparatus with geophones supported on a softly sprung frame to induce a seabed vibration of 20 Hz frequency, as observed during dredging, piling and other anthropogenic activities. The geophone internal mass caused the frame to vibrate in a controlled manner. Our results show that transition from ambient to anthropogenic vibrations induced an increase in activity and antennae beats in shore crabs, indicating perception of the vibratory stimulus and a higher stress level. There was also a trend on sex-specific responses to anthropogenic vibration, with males showing a higher activity level than females. However, no effect of anthropogenic vibrations was found upon oxygen consumption. These results show that anthropogenic underwater vibration induces behavioural responses in Carcinus maenas . This highlights the importance of evaluating man-made vibratory activities on coastal invertebrates and the necessity of evaluating anthropogenic effects on both sexes. Graphical abstract: Image 1 Highlights: Anthropogenic seabed vibration is perceived and stressful for shore crabs. Individuals exposed to vibration showed increased antennae beats and activity. Responses to seabed vibration showed sex-specific trends. Abstract : Manmade seabed vibrations are sensed and stressful for marine crabs.